Sanksi Hukum Terhadap Pelanggaran Pajak yang Dilakukan oleh Korporasi - Gusti Ayu Erlin Widyaningsih; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Tax is a source of state revenue which exceeds 80% (eighty percent) of the total revenue. Corporate tax is the main contributor to corporate tax, but corporate tax also has great potential as a tax evader. Avoiding corporate tax by excluding tax obligations and submitting incorrect SPT. The law is illegal and may be subject to statutory prohibition. Formulation of Research Tasks: how is the contribution of corporate taxes to state revenues and what are the legal sanctions for tax violations committed by corporations. The purpose of this study is to explain the contribution of corporate income tax to government revenues and to explain the legal sanctions for violations of corporate income tax. This research uses ideological studies with legal methods and conceptual approaches. The survey results show that the contribution of corporate income tax to state income and total corporate income is regulated in Article 4 (2) of the Income Tax Law, and the legal prohibition on corporate tax avoidance is regulated in Article 13a. The KUP Law in the form of administrative sanctions increases the low amount of tax charged by stating an increase in the tax account by 200% (two hundred percent).